2D Perovskite Seeding Layer for Efficient Air‐Processable and Stable Planar Perovskite Solar Cells. (2nd July 2020) - Hangoma, Pesi Mwitumwa; Shin, Insoo; Yang, Hyun‐Seock; Kim, Danbi; Jung, Yun Kyung; Lee, Bo Ram; Kim, Joo Hyun; Kim, Kwang Ho; Park, Sung Heum
Abstract: Despite the record power conversion efficiencies, inverted perovskite solar cells (PSCs) are still looking to overcome the challenge of moisture instability. This is mitigated by introducing 2D perovskite at the base of a 3D perovskite via coating of ethylenediamine bications on top of the hole transport layer of p–i–n planar configured devices. The cations induce thin 2D perovskite growth beneath the 3D perovskite to create a 2D/3D hybrid active layer. This 2D layer in turn acts as a template for the growth of relatively large grains compared to that of pure 3D perovskite films. This stems from the merging of grain boundaries. The hydrophobicity of the 2D/3D perovskite film consequently improves, as evidenced by a large contact angle of 93.1°, compared to 68.9° for the 3D perovskite film. Because there are fewer defects sourced from grain boundaries, the air‐processed 2D/3D perovskite devices yield a high power conversion efficiency of 15.02%, compared to 13.10% from 3D perovskite devices. When stored in moderately humid environment of 55% relative humidity, the 2D/3D devices exhibit longer stabilities, with 75% of their power conversion efficiencies maintained after 150 h, compared to a total loss in efficiency for 3D device in the same time frame. Abstract : When introduced beneath the 3D perovskite layer, the 2D perovskite seeding layer acts as a template for growth in the planar direction, resulting in an increase in perovskite grains with less and narrow grain boundaries. As a result, the hydrophobicity of the film increases resulting in better stability and improved efficiency when the films are processed in air.